Forecasting of Wind Speed Using an Interval-Based Least Square Method - Aslam, Muhammad; Albassam, Mohammed (Frontiers in Energy Research, 2022)
A new least square method (LSM) for time series analysis under indeterminacy is proposed in this work. The proposed LSM under indeterminacy is known as the neutrosophic least square method (NLSM). The NLSM is proposed to forecast wind speed when data are in the interval. The trended line under indeterminacy is introduced and applied using wind speed data. The time series plots under neutrosophic statistics are given. A comparative study shows that the proposed NLSM is more efficient and informative to apply for the forecasting of wind speed.